GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU PENDERITA ISPA DI WILAYAH KERJA PUSKESMAS PURWANEGARA 2 KABUPATEN BANJARNEGARA - Barni; Ratih Subekti (Jurnal Ilmiah Medsains, 2021)
One of the diseases that are often encountered is an acute respiratory infection (ARI). The incidence of ARI always ranks first of the 10 most common diseases in Indonesia. Factors causing ARI are environmental factors and behavioral factors. Health profile data for 2020 shows that ARI is ranked first out of the top 10 most common diseases in the work area of ​​Purwanegara 2 Health Center, Banjarnegara. The purpose of this research was to describe the knowledge, attitudes and behavior of patients with acute respiratory infections (ARI) in the working area of ​​Purwanegara 2 Public Health Center, Banjarnegara Regency in 2021. This research is quantitative descriptive. The research was carried out in the Purwanegara 2 Health Center Work Area, Banjarnegara Regency with a sample of 34 patients with ARI disease in April 2021. Sampling using purposive sampling technique. Data collection techniques used interviews with questionnaires regarding the level of knowledge, attitudes and behavior of patients with ARI. Analysis of the data used is descriptive statistics. The results showed that ARI patients who had knowledge level in the Good category were 6.47%, Enough as much as 2.94%, and Less as much as 70.59%. The attitudes of ARI sufferers are categorized as Good (100%), as well as the behavior of ARI patients are also in the Good category (100%). The conclusion of this study is that most of the knowledge possessed by patients is still lacking but their attitudes and behavior are in the good category. Therefore, it is necessary to make efforts to increase knowledge about ARI so that their attitudes and behavior are stronger based on proper knowledge of ARI. The conclusion of this study is that most of the knowledge possessed by patients is still lacking but their attitudes and behavior are in the good category. Therefore, it is necessary to make efforts to increase knowledge about ARI so that their attitudes and behavior are stronger based on proper knowledge of ARI.